PENGARUH KONSENTRASI KITOSAN DAN LAMA PENGASAPAN TERHADAP UJI ORGANOLEPTIK IKAN PATIN (Pangasius Sp) SALAI SEBAGAI RANCANGAN LEMBAR KERJA PESERTA DIDIK PADA PEMBELAJARAN BIOLOGI DI SMA - Anugrah Tifanny; Sri Wulandari; Elya Febrita (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: This study aims to determine the effect of chitosan concentration and smoking time on organoleptic tests of catfish (Pangasius sp) salai and its potential to produce student worksheet designs for food additives material in biology learning in class XI SMA. This research is a descriptive study using the Hedonic method which was carried out in July-September2020 at the laboratory of the Faculty of Teacher Training and Education, Riau University, Pekanbaru. In the organoleptic test on catfish (Pangasius sp) salai, involving 10 respondents consisting of 2 artisans of salai fish and 8 people as panelists. The results showed that respondents preferred fish with 3% chitosan concentration treatment and 3 days smoking on the appearance, scent, taste and texture aspects of salai catfish. The data from this research also has the potential to become a student worksheetdesign for food additives in biology learning in class XI high school.Key Words: Chitosan, Smoking Time, Pangasius Sp, Organoleptic, LKPD.